Current situation of Bitcoin management and use: perspectives from the world and recommendations for Vietnam - Hang Bui Thi Thu; Huy Dinh Tran Ngoc; An Phan Thuy; Ngoc Nguyen Thi Bich; Duyen Huynh Thi My (Zielona Góra: Faculty of Economics and Management Press)
The research aimed to evaluate suitability of Bitcoin and its platform in emerging markets such as Vietnam. We used qualitative analysis combined with data collection method published, statistics, analysis, synthesis, comparison, to generate qualitative comments and discussion; evaluate results, the article analyzed and evaluated the impacts of Bitcoin and virtual currency on society of Vietnam, both positive and negative sides.
Keywords: bitcoin; virtual currency; cryptocurrencies; Vietnam; waluta wirtualna; kryptowaluty; Wietnam